Adaptive Synchronization of Chaotic Genesio–Tesi Systems Via A Nonlinear Control - Sadat Alaviyan Shahri, Esmat (International Journal of Engineering and Technology, 2018)
The paper presents the stabilization and adaptive synchronization problem of a class of chaotic systems (Genesio–Tesi system) with three unknown parameters. A novel nonlinear control effort is proposed and an adaptive strategy is presented in order to the states of two Genesio–Tesi systems were asymptotically synchronized. The known Lyapunov method guarantees the presented stability analysis and design. An illustrative simulation result is given to demonstrate the effectiveness of the proposed chaos synchronization scheme.